IMPLEMENTATION OF PERFORMANCE PLANNING AT THE COMMUNITY AND RURAL EMPOWERMENT, POPULATION, AND CIVIL REGISTRY AGENCY OF NORTH SUMATERA PROVINCE - Tampubolon, Silvia Marsinta; Siahaan, Asima Yanty S; Sihombing, Tunggul (DIA: Jurnal Administrasi Publik, 2024)
The important factor which indicates the effectiveness and efficiency of an organization is the organizational complete planning in implementing its vision and mission. North Sumatera province grants B accreditation in its SAKIP and RB which indicates that it needs improvement in terms of work Unit and the commitment of performance management. The Community and Rural Empowerment, Population, and Civil Registry Agency of North Sumatera Province, as one of the Regional Apparatus Organizations, has RENSTRA (Strategic Plan Document). However, there is no standard procedure in the process of determining the performance goal and target. Therefore, the objective of the research is to find out and describe in detail the performance planning in the Agency. The research employs qualitative approach. The result of the research shows that the Agency has implemented the management system of employee performance based on Regulation of the Minister for Administrative Reform and Bureaucratic Reform of the Republic of Indonesia No. 6/2022. However, there are still many things that have to be improved such as determining the work standard in the process of organizing employee Performance Targets which focuses only based on the time achievement and not based on the achievement of the quality of performance. It is found that the process of performance planning in the Agency is not maximal in its performance communication. It can be seen from the failure to involve all employees in formulating the goal and target